Exploring the relationship between mindset and psychological factors linked to doping. Issue 4 (October 2022) - Wilkins, Luke; Dunn, Anna; Zoob Carter, Barnaby N.; Boardley, Ian D.
Abstract: Mindset refers to the way in which one attributes his or her abilities and traits as either 'fixed' (e.g., immutable), 'growth' (e.g., highly malleable), or somewhere in between. It is possible that mindset may be related to psychological factors linked to doping – such as doping moral disengagement (MD) and doping self-regulatory efficacy (SRE) – though no research as yet has confirmed this. In the present study, 322 student-athletes completed a questionnaire pack measuring mindset and various psychological factors linked to doping. Structural equation modeling provided strong support for all study hypotheses. Specifically, we established: (a) mindset positively predicted doping SRE, (b) mindset negatively predicted doping MD, (c) doping MD positively predicted susceptibility to intentional and inadvertent doping, (d) doping MD negatively predicted anticipated guilt, (e) anticipated guilt negatively predicted susceptibility to intentional and inadvertent doping. In addition, significant negative correlations were found between MSA and doping moral disengagement ( r  = -.19, p < .01), MSA and susceptibility to inadvertent doping ( r  = -.11, p < .01), MMC and moral disengagement ( r  = -.12, p < .05), and MMC and susceptibility to inadvertent doping ( r  = -.13, p < .05). A significant positive correlation was found between MSA and doping SRE ( r  = .23, p < .01). Implications of the findings include the potential for early identification of athletes at risk of doping based on their mindset. Future research should look to explore the effectiveness of mindset interventions on reducing transgressive doping attitudes and behaviours.